A Survey on Secure Binary Image Steganography Based on Minimizing the Distortion on the Texture - Mol M, Honey; Reji P.I, Prof.Mrs. (IJRDO -Journal of Computer Science Engineering, 2016)
Many of the binary image steganographictechniques only consider the flipping distortion according tothe HVS( Human Visual System), which will be not secure .Here, a binary image steganographic scheme is to minimize theembedding distortion on the texture . To extract thecomplement, rotation, and mirroring-invariant local texturepatterns (crmiLTPs)from the binary image . The weighted sumof crmiLTP changes when flipping one pixel is then used tomeasure the flipping distortion corresponding to that pixel. Bytesting on simple binary images and the new image data set,the results shows that the proposed scheme can well describethe distortions on both visual quality and statistics.This schemegenerates the cover vector by dividing the scrambled imageinto super pixels. Experimental results show that the proposedscheme can achieve statistical security without degrading theimage quality or the embedding capacity. In this paperdescribes survey on image steganographic techniques andsteganographic techniques used with different cryptographicalgorithms, to provide extra layer of Security.